The Influence of Inflation, DER, ROA, and NPM in Stock Returns in Mining Companies Listed on the Indonesia Stock Exchange - Iis RInda Amaroh; Hetty Muniroh (SIMAK, 2026)
This study aims to analyze the factors influencing stock returns as a basis for investment decision-making. Stock return serves as an important indicator reflecting a company’s performance as well as investors’ confidence in its future prospects. Higher levels of return tend to increase the company’s attractiveness to investors. Therefore, understanding the determinants of stock returns is essential to assist investors in managing risk and optimizing investment gains. This study aims to examine and verify the effect of inflation, Debt to Equity Ratio (DER), Return on Assets (ROA), and Net Profit Margin (NPM) on stock returns. This research focuses on mining companies listed on the Indonesia Stock Exchange during the period 2021–2024, with a population of 46 companies. The sampling method used was purposive sampling, resulting in a sample of 28 companies. The data analysis technique employed was multiple linear regression analysis. The results show that inflation has a positive but insignificant effect on stock returns, Debt to Equity Ratio (DER) and Return on Assets (ROA) have a negative but insignificant effect on stock returns and Net Profit Margin (NPM) has a positive but insignificant effect on stock returns.